Causes of spontaneous death and euthanasia in dogs: A background study in Bahia, Brazil - Freitas JL; Andrade TS; Martins Filho EF; D'Soares CS; Souza ACSN; Silva AWO; Leal PV; Peixoto TC (Veterinární Medicína, 2021)
Understanding the causes of death in dogs enhances the diagnostic capabilities of veterinarians, as well as reduces animal mortality. Studies on this topic assist in the control and prophylaxis of epidemics and in structuring public health programmes. In total, 1 355 necropsy reports of dogs filed at the Veterinary Pathology Laboratory of the Federal University of Bahia, Northeast, Brazil (2005-2017) were analysed. The epidemiological information and anatomopathological diagnoses were obtained. The diagnosed diseases were classified into 10 categories. The frequency of the zoonoses, the overall age of the death (AD) of the dogs, and the AD of the dogs for each disease category were determined. Infectious and parasitic diseases were the most frequent primary causes of death in puppies (44.62%) and adult dogs (26.52%). In elderly dogs, most deaths occurred due to neoplasms (42.37%). Distemper (10.46%) was the most prevalent condition. A high frequency of zoonoses (6.12%) and a high death rate caused by diseases that could have been prevented (15.06%), such as distemper, parvovirus and canine visceral leishmaniasis, were reported. The AD in the population studied was eight years. The results confirmed the hypothesis of a high death rate in dogs in the state of Bahia, Northeast, Brazil, because of preventable infectious diseases.